Dotting the I's and crossing the T's: autonomy and/or beneficence? The ‘fetus as a patient’ in maternal-fetal surgery - Rodrigues, H. M. L. (Journal of medical ethics, 2013)
Chervenak and McCullough, authors of the most acknowledged ethical framework for maternal-fetal surgery, rely on the ‘ethical-obstetrical’ concept of the fetus as a patient in order to determine what is morally owed to fetuses by both physicians and the women who gestate them in the context of prenatal surgery. In this article, we reconstruct the argumentative structure of their framework and present an internal criticism. First, we analyse the justificatory arguments put forward by the authors regarding the moral status of the fetus qua patient. Second, we discuss the internal coherence and consistency of the moral obligations those authors derive from that concept. We claim that some of the dilemmas their approach is purported to avoid, such as the debate about the independent moral status of the fetus, and the foundation of the moral obligations of pregnant women (towards the fetuses they gestate) are not, all things considered, avoided. Chervenak and McCullough construct the obligations of physicians as obligations towards entities with equal moral status. But, at the same time, they assume that the woman has an independent moral status while the moral status of the fetus is dependent on the decision of the woman to present it to a physician for care. According to the logic of their own argumentation, Chervenak and McCullough implicitly admit a different moral status of the woman and the fetus, which will lead to different ascription of duties of the physician than those they ascribed.